Guidance and Counselling for Pupils with Special Educational Needs in Accra, Ghana: Implications for Inclusive Education (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Pupils with special educational needs require guidance and counselling services to overcome their social and psychological challenges. The study explored available guidance and counselling services in three special schools in Ghana. The concurrent triangulation mixed- method design was used. The samples of pupils (88) and staff (3), comprising administrators and guidance and counselling coordinators were purposively selected for the study. Data were collected with a questionnaire and an interview guide. Quantitative data was analysed using descriptive statistics, specifically, frequencies and percentages while in the qualitative analysis, the thematic approach was used. The importance of guidance services was prevalent. The facility enabled discussions regarding pupils’ educational goal construction, career plan development and solving relationship problems among pupils, their staff and parents. Regional Education officers were subsequently recommended to liaise with their counterparts at the Guidance and Counselling and Special Education Regional offices to monitor special schools, which will enable them to ensure widened service access and effective implementation.
Keywords: Guidance and Counselling; Inclusive Education; Special Schools; Special Educational Needs